2011
DOI: 10.1002/ps.2240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of glyphosate plus urea phosphate in the greenhouse and the field

Abstract: The application of UPP as an adjuvant could increase the efficacy of glyphosate and make it possible to achieve effective control of weeds with glyphosate at lower dose. Moreover, UPP showed less causticity to spraying tools and presented less of a health hazard. Therefore, UPP is accepted as being a new, effective and environmentally benign adjuvant for glyphosate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Other adjuvants (inert ingredients), such as urea (Li et al 2012) and commercially formulated products, can also be used to counter the effects of hard water. Further, be aware that different commercial glyphosate formulations contain different adjuvants and can vary in efficacy (Chikoye, Lum, and Udensi 2010).…”
Section: Step Three: Properly Calibrate Spray Equipmentmentioning
confidence: 99%
“…Other adjuvants (inert ingredients), such as urea (Li et al 2012) and commercially formulated products, can also be used to counter the effects of hard water. Further, be aware that different commercial glyphosate formulations contain different adjuvants and can vary in efficacy (Chikoye, Lum, and Udensi 2010).…”
Section: Step Three: Properly Calibrate Spray Equipmentmentioning
confidence: 99%
“…The results are similar to those of Bekeko (2013), who found that lower concentrations of urea and common salt enhanced the phytotoxicity level of glyphosate on parthenium weed. Similarly, urea phosphate (UPP) as an adjuvant could increase the efficacy of glyphosate and make it possible to achieve effective weed control with glyphosate at lower doses (Pingliang et al 2012).…”
Section: Experiments 1: Effect Of the Treatments On The Common Reed C...mentioning
confidence: 99%
“…En una formulación líquida de sulfato de amonio el porcentaje usado debe ser equivalente. Otros adyuvantes (ingredientes inertes), como la urea (Li et al 2012) y productos comercialmente formulados, pueden ser usados de la misma forma para contrarrestar los efectos del agua pesada. Adicionalmente, esté consciente que las diferentes formulaciones de glifosato contienen diferentes adyuvantes y pueden variar en eficacia (Chikote et al 2010).…”
Section: Paso Tres: Calibrar Apropiadamente El Equipo De Aplicaciónunclassified